The Phenomenal Existentialism in Lyrics of the Bodyslam Aritsts - ไรแสง ศรุตานนท์ (Buddhamagga, 2018)
This article aims to study the phenomenal existentialism in the Bodyslam band song’s lyrics. It is a philosophical phenomenon that seeks the philosophy of existentialism is considered to find the essence makes the mind out of reality. The truth is the existence of individual, environment, and self-accumulation those choose from the beginning until the present which is a useful philosophy of self-actualization. This philosophy draws attention to the pursuit of truth outside the human being, finding no way to find and know it. To understand the reality that exists within the human being, each person must practice and know by himself. The existentialism line up in Bodyslam lyric songs especially in the content of the theme of songs those are outstanding about the world, nature of life and human relations. The "New phenomena" philosophy of existentialism was created through a "music language" that built the identity of the Bodyslam, therefore, they are popular across the country.